Sound insulation prediction method for single and spot laminated multilayer panels. Issue 3 (September 2022) - Mansilla, Joaquín; Bender, Laurence; Pepino, Leonardo; Brito, María Sol
Single-leaf panels made from homogeneous and isotropic materials are commonly used in buildings. However, it is often necessary to add various layers of the same or different materials in order to increase the acoustic insulation. This article presents a prediction method for the calculation of the sound reduction index that comprises single panels and multilayer panels joined together using spot techniques, such as by screws. The method is based on previous single-leaf panel models extended to multilayer structures. The predicted values are compared with panel measurements obtained according to ISO 140-3. The sound reduction index R in third octave bands, the weighted sound reduction index Rw, and the spectral adaptation terms ( C, Ctr ) are examined. In addition, predictions from two commercial software tools are evaluated and compared. Statistically, the results show that the proposed method gives values that agree well with the measurements, both for single and multilayer panels.